Recent advances of nanomedicine technology in the diagnosis and treatment of acute kidney injury - Zhao Ming-yue; Lin Yong-tao (Linchuang shenzangbing zazhi)
As a common clinical emergency and critical illness, acute kidney injury（AKI）is frequently accompanied by severe short/long-term complications.It is a major health problem with high morbidity and high mortality.Nanomaterials are a new type of multifunctional materials.In recent years, nanomaterials have been applied extensively in the fields of bioimaging, early cancer diagnosis and drug delivery, providing strong material and technical supports for medical diagnosis and treatment.More and more nano-pharmaceuticals are clinically transformed so as to provide novel solutions diagnosing and treating kidney diseases.This review offered a brief overview of diagnosing and treating AKI with nanomedicine technology.